Resistance to d-Cycloserine in the Tubercle Bacilli: Mutation Rate and Transport of Alanine in Parental Cells and Drug-Resistant Mutants - David, Hugo L. (1971)
A single transport system was found to accumulate l- and d-alanine, glycine and d-serine in Mycobacterium tuberculosis. The results of inhibition experiments suggested that the antibiotics d-cycloserine and O-carbamyl-d-serine were also transported by the alanine-glycine-d-serine system. A d-cycloserine-resistant permease-competent (d-CS(r)/perm(+)) mutant and a d-cycloserine-resistant permease-defective (d-CS(r)/perm(−)) mutant were isolated. The d-CS(r)/perm(−) mutant was not found to be more resistant to the drug than was the d-CS(r)/perm(+) mutant. The data were consistent with the conclusion that resistance to d-cycloserine in the tubercle bacilli is primarily due to mutations in the gene(s) controlling the enzyme d-alanyl-d-alanine synthetase. The mutation rate was calculated to be about 10(−10) mutations per bacterium per generation.